Henry More’s “Spirit of Nature” and Newton’s Aether - Joseph, Jacques (Teorie vědy / Theory of Science, 2017)
The paper presents the notion of “Spirit of Nature” in Henry More and describes its position within More’s philosophical system. Through a thorough analysis, it tries to show in what respects it can be considered a scientific object (especially taking into account the goals of More’s natural philosophy) and in what respects it cannot. In the second part of this paper, More’s “Spirit of Nature” is compared to Newton’s various attempts at presenting a metaphysical cause of the force of gravity, using the similarities between the two to see this notorious problem of Newton scholarship in a new light. One thus sees that if Newton drew from Stoic and Neo-Platonic theories of aether or soul of the world, we need to fully acknowledge the fact that these substances were traditionally of a non-dualistic, half-corporeal, half-spiritual nature. Both More’s “Spirit of Nature” and Newton’s aether can thus be understood as different attempts at incorporating such a pneumatic theory into the framework of modern physics, as it was then being formed.